GESTUR PENARI GANDRUNGDALAM PERANCANGAN KURSITERAS - Arum Wahyuningsih (SULUH: Jurnal Seni Desain Budaya, 2020)
To make a furniture product, you must follow the correct steps,from designing to the finishing stage. A mature design certainlyrequires a research process stage, the author takes the conceptof Gandrung Dance from Banyuwangi as the idea of creating aterrace chair. The Banyuwangi Gandrung Dance is a traditionaldance of the Osing Banyuwangi tribe. The variety of movementsand clothing styles are very interesting if you look at the forms ofdecoration and the meaning of the basic colors of clothing. Fromthe variety of movements and decorations, it can be exploredand then developed into the concept of designing a terracechair. In the design process, it begins with making severalsketches, then a sketch is selected for the design determinationwhich is then made a working drawing, followed by thepreparation of materials for production to planning theproduction process.